Carta de Roberto H. Todd a Pedro Monclova - Todd, Roberto H.; Monclova, Pedro (My University, 1934)
Los compontes
Keywords: Valle Atiles, Francisco del, 1852-1928; Blanco Sosa, Julián E., 1830-1905; Muñoz Barrios, Manuel; Ferrer Hernández, Gabriel; Guillermety, Fidel; Quiñones Quiñones, Francisco Mariano, 1830–1908